Obesity Patterns among Women in a Slum Area in Brazil (Journal of Health, Population and Nutrition, 2011)
High-energy diet and sedentary lifestyle fail to completely explain the epidemic of obesity in developing countries. In this cross-sectional survey, the prevalence and patterns of overweight/obesity were assessed among women in a slum in Brazil. Using anthropometric measurements, shorter form of the International Physical Activity Questionnaire (IPAQ), and a 24-hour diet recall questionnaire, data were collected from 632 women aged 20-60 years. The prevalence of overweight and obesity was 29% and 17% respectively. Physical inactivity was found in 17% of the women; 12% of them had short stature, and 44% had energy intake below the recommended dietary allowance. Results of multiple logistic regression showed that overweight/ obesity differed significantly (p